Avaliação do efeito do ultrassom terapêutico sobre a disseminação de tumor de Walker 256 implantado no subcutâneo do rato wistar - Araujo, Milena do Carmo (2020)
Results for the use of therapeutic ultrasound in experimental models of cancer are inconclusive regarding tumor growth and metastasis induction. The presence of malignancy is a contraindication for therapeutic ultrasound use, despite the absence of well-established scientific reasons. The study aimed to evaluate the effect of therapeutic ultrasound on Walker carcinosarcoma, notably on tumor growth and metastasis development. Walker carcinosarcoma was inoculated subcutaneously on the back of Wistar rats. The animals were randomly distributed into three groups: Continuous (n = 12), submitted to ultrasound in the continuous mode; Pulsed (n = 11), in which the animals were treated with pulsed mode ultrasound; and control (n = 11), in which the sham use of ultrasound was performed. Treatment was carried out for seven days, with the application of ultrasound for 9-15 minutes at a frequency of 1 MHz, in the continuous and pulsed emission modes, with an intensity of 1 W/cm² SATA (spatial average temporal average) and 1 W/cm² SATP (spatial average temporal peak), respectively. The treatment using continuous and pulsed US did not change the temporal progression or tumor growth rate; it did not influence animal survival, either. Additionally, metastatic organ involvement was similar in all groups. The use of ultrasound in aforementioned modes, did not affect the growth of Walker carcinosarcoma, or the development of metastases